Parameter Optimization Design of the Aged Chair Auxiliary Standing Mechanism - Zhou Hui; Qin Baorong; Zhang Dongdong; Xiang Bingle; Bao Jiahua; Wang Zhengxing (Jixie chuandong)
The working theory of the aged chair auxiliary standing mechanism is introduced,the force transmission characteristic analysis for auxiliary standing mechanism is carried out,and the motion regular of transmission angle for this mechanism is obtained. For the problem that the traditional auxiliary standing mechanism have the poor force transmission characteristic and mechanism efficiency,a motion simulation and parametric modeling is carried out by using the multi- body dynamics simulation software ADAMS. Then,the optimization analysis with the target that transmission angle of auxiliary standing four- bar mechanism obtain maximum value is carried out. Finally,the parameter effecting on the main design variables of transmission angle is defined. The results show that transmission angle is obviously improved after the optimization,the force transmission characteristics and mechanism efficiency of auxiliary standing mechanism are improved,as the same time front rake level of mechanism is increased to help the aged standing.